Chromium distribution between slag and non-carbon saturated metal phases under changing partial pressure of carbon monoxide - X. Pan (The Southern African Institute of Mining and Metallurgy, 2004)
Slag-metal equilibrium experiments were conducted at 1500ºC and 1580ºC under 0.03 atm, 0.05atm and 0.83 atm CO partial pressures using silica and Cr-oxide crucibles. The complex slags belonged to SiO2-CaO-Al2O3-MgO-FeOx-CrOxand the metal phase to the Cr-Fe-C-Si-(S)systems. The carbon saturation of the metal phase was avoided using oxide crucibles and thus the results are pertinent to ferrochromium refining slags and processes. From equilibrium data and thermodynamic calculations the CrO /(CrO+Cr2O3) ratio in the slag was determined as 0.75, 0.80and 0.86 under 0.83 atm and 0.05 atm of CO pressure at 1500ºC and 0.03 atm and CO pressure at1580ºC respectively. The results clearly demonstrated that a higher chromium content of the metal results in higher Cr in the slag, and chromium in slag decreases with increasing SiO2. The results were also sensitive to the crucibles used as these oxide crucibles saturated the slag either with respect to SiO2or Cr-oxides. It was also demonstrated that the relative amount of CrO in the slag was higher when SiO2crucibles were used in accord with thermodynamic calculations. Iso-concentration curves for carbon and chromium of the metal phase in equilibrium with the slag were drawn on pseudo ternary SiO2–(AI2O3+CaO+MgO)–(Cr2O3+Fe2O3) diagram. The activity coefficients and activities of carbon and chromium of the metal phase were also calculated from the experimental data and available thermodynamics information and were plotted as iso-activity curves in the same pseudo ternary diagram. Keywords: Chromium, slag, equilibrium